2022
DOI: 10.1038/s41598-022-06970-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA editing patterns in Huntington’s disease

Abstract: Huntington’s disease (HD) is a neurodegenerative disease. MicroRNAs (miRNAs) are small non-coding RNAs that mediate post-transcriptional regulation of target genes. Although miRNAs are extensively edited in human brains, the editome of miRNAs in brains of HD patients is largely unknown. By analyzing the small RNA sequencing profiles of brain tissues of 28 HD patients and 83 normal controls, 1182 miRNA editing sites with significant editing levels were identified. In addition to 27 A-to-I editing sites, we iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 94 publications
3
15
0
Order By: Relevance
“…RNA editing is a concerned mechanism in eukaryote and can alter the primary sequences of RNA transcripts by deleting, inserting and modifying residues ( Nishikura, 2010 ). miRNAs are edited in several ways, including 3′ non-templated addition (3′-NTA) ( Burroughs et al, 2010 ), Adenosine-to-Inosine (A-to-I) editing performed by adenosine deaminase (ADAR) and C-to-U (Cytidine-to-uridine) editing performed by apolipoprotein B mRNA editing polypeptide-like (APOBEC) enzymes ( Galeano et al, 2012 ; Guo et al, 2022 ). Many studies have reported that changes in miRNA editing could both play a role in tumor pathogenesis and progression, and be used as early and specific biomarkers of selected forms of cancer ( Guo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…RNA editing is a concerned mechanism in eukaryote and can alter the primary sequences of RNA transcripts by deleting, inserting and modifying residues ( Nishikura, 2010 ). miRNAs are edited in several ways, including 3′ non-templated addition (3′-NTA) ( Burroughs et al, 2010 ), Adenosine-to-Inosine (A-to-I) editing performed by adenosine deaminase (ADAR) and C-to-U (Cytidine-to-uridine) editing performed by apolipoprotein B mRNA editing polypeptide-like (APOBEC) enzymes ( Galeano et al, 2012 ; Guo et al, 2022 ). Many studies have reported that changes in miRNA editing could both play a role in tumor pathogenesis and progression, and be used as early and specific biomarkers of selected forms of cancer ( Guo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are edited in several ways, including 3′ non-templated addition (3′-NTA) ( Burroughs et al, 2010 ), Adenosine-to-Inosine (A-to-I) editing performed by adenosine deaminase (ADAR) and C-to-U (Cytidine-to-uridine) editing performed by apolipoprotein B mRNA editing polypeptide-like (APOBEC) enzymes ( Galeano et al, 2012 ; Guo et al, 2022 ). Many studies have reported that changes in miRNA editing could both play a role in tumor pathogenesis and progression, and be used as early and specific biomarkers of selected forms of cancer ( Guo et al, 2022 ). The A-to-I edited miR-376a inhibits glioma cell migration and invasion by targeting AMFR, and fails to inhibit the original target RAP2A ( Choudhury et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be elucidated whether the triggering factor is a unique component (e.g., Ago2 downregulation [ 28 ]) or a more general mechanism in humans. Also, it is uncertain if changes in RISC components could explain miRNA editing patterns in HD [ 13 ]. The study of pre-symptomatic HD patients (i.e., Vonsattel grades HD0-1) or humanized cell models (e.g., iPSC) would help address these questions.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we and others have shown that mHtt binds to Ago2 protein [ 34 , 41 , 42 ], whereas transient overexpression of mHtt in cells and mice leads to higher Ago2 expression and widespread alterations in mature miRNA levels [ 34 ]. Furthermore, post-mortem studies have detected changes in mature miRNA expression and editing profiles in the brains of HD mice and humans [ 13 , 20 22 , 27 , 29 , 30 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported significant miRNA editing patterns in HD patients, including A to I and C to U nucleotide changes [ 70 ]. Intriguingly, mir-10b-5p was edited to have an additional cytosine at 5’-end, and has previously been linked to HD pathogenesis [ 71 , 72 ].…”
Section: Mirnas In Dementia-related Diseasesmentioning
confidence: 99%